Transparancy Level of Compliance and Implementation Government Regulation Number 55 Of 2022 For Taxpayers in The Bekasi City - Andaningsih, I Gusti Putu Ratih; Nugrahanti, Trinandari Prasetyo; Murti, Wahyu (Lembaga Publikasi Ilmiah Nusantara, 2024)
The author in conducting this research conducted research related to PP No 55 of 2022 concerning improvements regarding the regulations and treatment of income tax for taxpayers.The purpose of this study is to find out more deeply about the level of measurement and implementation of PP No 55 of 2022 regarding the determination and implementation of income tax on taxpayers,especially in the city of Bekasi and its surroundings. The research method used is a symmetric qualitative descriptive method with a factor analysis content approach using data from 25 informants during the period March 2023-June 2023.Researchers used in person and online interviews in the retail sector and manufacturers who are tax exempt and corporate taxpayers in the Bekasi City Regions.The research is very useful for knowing the level of compliance of individual PPh taxpayers and corporate PPhtaxpayers,especially for regarding transparency ,compliance and implementation of PP No 55 of 2022 concerning the application of individual taxes and corporate PPh taxpayers.The limitations of this research are only limited to the level of compliance and implementation of taxpayers in the category of retail and manufacturers, especially individual taxpayers and corporate taxpayers in the Bekasi City areas.The research contribution is to increase the income of the national tax sector for the imposition of income tax on individual taxpayers and corporate taxpayers the Bekasi City areas and their surroundings.The results of the research of transparency,compliance and increase implementation in awareness of paying taxes for entrepreneurs.